Beneficial effects of melatonin on diaphragmatic contractility and fatigability in Escherichia coli endotoxemic rats - Kurcer, Z; Iraz, M; Kelesyilmaz, N; Kilic, N; Olmez, E (Georg Thieme Verlag Kg, 2006)
Sepsis impairs diaphragmatic contractility and endurance capacity and increases diaphragmatic fatigability. Several investigations have shown that administration of a number of free radical scavengers, such as N-acetylcysteine (NAC), protects the diaphragm from the development of endotoxin-mediated diaphragmatic dysfunction. The aim of this study was to evaluate the effects of melatonin (CAS 73-31-4), a naturally occurring potent antioxidant, on diaphragmatic contractility and lipid peroxidation as a marker of oxidative stress in endotoxemic rats. Rats were randomly divided into four groups: control group, endotoxemic group, melatonin group and endotoxemic plus melatonin group. Melatonin was administered by intraperitoneal injection 30 min before endotoxin inoculation to animals. Diaphragmatic function and malondialdehyde (MDA) level analysis as an indicator of lipid peroxidation were assessed 17 h after endotoxin or saline inoculation. Endotoxemia decreased the tensions generated in response to all frequencies of stimulation and increased the development of diaphragm fatigue and diaphragmatic MDA levels. The effects of endotoxemia on diaphragmatic contractions and fatigability were reversed and returned to control levels by melatonin administration. However, melatonin did not prevent the increase in muscle MDA content. In conclusion, the present study demonstrated that melatonin attenuated the endotoxin-induced impairment of diaphragm function. This effect of melatonin does not seem to be related to its antioxidant properties.
Keywords: andoxidants; CAS 73-31-4; endotoxemia; melatonin, effect on diaphragmatic ftmction